2019
DOI: 10.1167/iovs.19-26580
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prevalence of Myopia and Myopic Maculopathy in a Japanese Population: The Hisayama Study

Abstract: PURPOSE. To examine trends in the prevalence of myopia and myopic maculopathy in a general Japanese population. METHODS. Residents of a Japanese community aged 40 years and older participated in surveys conducted in 2005, 2012, and 2017. Each participant underwent comprehensive eye examinations that included measurements of refractive error, axial lengths, and color fundus photography. Myopic maculopathy was defined according to the criteria of the Meta-analysis of Pathologic Myopia Study Group classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…High myopia (≤−6.0 diopters) was identified in a half (50%) of our four Japanese patients and its prevalence is similar to that of RP2-RD in a different cohort (12/25, 48.0%) (Jayasundera et al, 2010). This prevalence of high myopia in RP2-RD was much higher than that of the general Japanese population (5.8-11.8%) reported in previous reports (Ueda et al, 2019;Yotsukura et al, 2019). Central visual loss was also found in all four patients, which was likely caused by macular dysfunction in RP2-RD.…”
Section: Genotype-phenotype Associationsupporting
confidence: 72%
“…High myopia (≤−6.0 diopters) was identified in a half (50%) of our four Japanese patients and its prevalence is similar to that of RP2-RD in a different cohort (12/25, 48.0%) (Jayasundera et al, 2010). This prevalence of high myopia in RP2-RD was much higher than that of the general Japanese population (5.8-11.8%) reported in previous reports (Ueda et al, 2019;Yotsukura et al, 2019). Central visual loss was also found in all four patients, which was likely caused by macular dysfunction in RP2-RD.…”
Section: Genotype-phenotype Associationsupporting
confidence: 72%
“…Figure 1 shows the selection process of studies identified through the database search with 3954 initial records. Altogether, 12 studies (13 datasets as one study provided two crosssectional with two different samples) 20 with 58 558 subjects were included for qualitative synthesis. The basic characteristics of included studies are given in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In Korea, between 2008 and 2011, myopia prevalence in 20 to 29-year-olds was 78.9% and increased in 2013 to 2014 to 81.3%, and in Japan, myopia in adults ≥ 40 years increased from 37.7% in 2005 to 45.8% in 2017. 17 Meta-analysis of studies in Europe show that the age standardized prevalence of myopia increased in older adults, where myopia in the 50 to 79 year age group was observed to be higher by 5.7% in those born later (23.5%) in a decade compared to those born earlier (17.8%). 18 As a result of the rising prevalence of myopia, it follows that there could be an increase in the prevalence of high myopia.…”
Section: Myopia Incidence and Prevalencementioning
confidence: 99%
“…38,39 Of these, myopic retinopathy or MMD is fast emerging as one of the leading causes of blindness in East Asia and else-where. 15,17,40 A recent meta-analysis found a pooled prevalence of MMD in the world population of 2.1% (increasing from 1.3% in the 40-49 age group to 4.5% in the 70+ age group) 41 and found a higher frequency of MMD from data reported from 2007 to 2019 compared to 1993 to 2006. Vision impairment from MMD was estimated to have affected 10 million people (0.13% of world's population) in 2015 and, if the trajectory for the rising prevalence of myopia and high myopia continues at the same pace, it is set to grow to nearly 56 million (0.6%) by the year 2050.…”
Section: Life-course Of Myopiamentioning
confidence: 99%